Review of simultaneous treatment with intradetrusor onabotulinumtoxinA injections during transurethral prostate surgery for men with bladder outlet obstruction and overactive bladder - Chun-Kai Hsu; Wan-Ling Young; Shu-Yu Wu (Tzu-Chi Medical Journal, 2025)
Bladder outlet obstruction (BOO) is common in males with benign prostate enlargement (BPE) and often presents with different lower urinary tract symptoms. Overactive bladder (OAB) has been reported to be related to BOO, although it can also be idiopathic. The storage symptoms of BOO are often similar to those of OAB. The etiology and pathophysiology of both BPE and OAB are multifactorial with metabolic syndrome known as one of the factors. As of today, transurethral prostate surgery remains the gold standard for treating BOO associated with BPE. Intradetrusor onabotulinumtoxinA (BoNT-A) injections have been shown to be effective in treating OAB. However, they are usually administered after transurethral prostate surgery. In view of the strong therapeutic effects of both surgery and injections, the feasibility of combining them in one setting to increase patient comfort, convenience, and possibly results while decreasing costs is appealing to physicians. However, patient safety and possible complications have to be considered. In this article, we review available studies of concurrent intradetrusor BoNT-A injections during transurethral prostate surgery. Although there is no definitive evidence supporting the concurrent use of intradetrusor BoNT-A during transurethral prostate surgery, there are no reports of increased complications too. Further large-scale randomized controlled trials would be necessary to validate the feasibility of combining the treatments in one setting and observe for possible complications.